Hepatitis B Virus HBx Activates Notch Signaling via Delta-Like 4/Notch1 in Hepatocellular Carcinoma. - Pornrat Kongkavitoon; Pisit Tangkijvanich; Nattiya Hirankarn; Tanapat Palaga (PLoS ONE, 2016)
Hepatitis virus B (HBV) infection is one of the major causes of hepatocellular carcinomas (HCC). HBx protein encoded in HBV genome is one of the key viral factors leading to malignant transformation of infected cells. HBx functions by interfering with cellular functions, causing aberration in cellular behaviour and transformation. Notch signalling is a well-conserved pathway involved in cellular differentiation, cell survival and cell death operating in various types of cells. Aberration in the Notch signalling pathways is linked to various tumors, including HCC. The role of HBx on the Notch signalling in HCC, however, is still controversial. In this study, we reported that HBV genome-containing HCC cell line HepG2 (HepG2.2.15) expressed higher Notch1 and Delta-like 4 (Dll4), compared to the control HepG2 without HBV genome. This upregulation coincided with increased appearance of the cleavage of Notch1, indicating constitutively activated Notch signalling. Silencing of HBx specifically reduced the level of Dll4 and cleaved Notch1. The increase in Dll4 level was confirmed in clinical specimens of HCC lesion, in comparison with non-tumor lesions. Using specific signalling pathway inhibitors, we found that MEK1/2, PI3K/AKT and NF-κB pathways are critical for HBx-mediated Dll4 upregulation. Silencing of HBx clearly decreased the level of phosphorylation of Akt and Erk1/2. Upon silencing of Dll4 in HepG2.2.15, decreased cleaved Notch1, increased apoptosis and cell cycle arrest were observed, suggesting a critical role of HBx-Dll4-Notch1 axis in regulating cell survival in HCC. Furthermore, clonogenic assay confirmed the important role of Dll4 in regulating cell survival of HBV-genome containing HCC cell line. Taken together, we reported a link between HBx and the Notch signalling in HCC that affects cell survival of HCC, which can be a potential target for therapy.